52.4k views
4 votes
Given: -7(x+2)+4x=6(2x-4) prove: x=2/3

User Phildobbin
by
4.9k points

1 Answer

6 votes

Answer:

2/3

Explanation:

multipy (X+2) by 7 the you multiply (2x-4) by 6 I.e

-7×X- (-7×2)+4x=6×2x-6×4

-7x-14+4x=12x-24

collect like terms

-7x+4x-12x=-24+14

-15x=10

divide both side by -15, so that X can stand alone

-15x/-15=-10/-15

-15 cancels -15, minus cancels minus

X=10/15

X=2/3

User Toyos
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.